1990
DOI: 10.1111/j.1749-7345.1990.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Three Cultured Algal Species (Isochvysis galbana, Chaetoceros gracilis and Chaetoceros calcitrans) Used as Food for Bivalve Larvae

Abstract: Fatty acids of three cultured unicellular algae wldely used in aquaculture (Isochrysis galbana, clone T‐iso, Chaetoceros calcitrans, and Chaetoceros gracilis) were analyzed in detail by gas‐liquid chromatography and mass spectrometry. Fatty acid compositions of the individual species, harvested at monthly intervals during a four month period, showed a very consistent pattern. Shorter chain (C16) fatty acids accounted for more than 70% of total fatty acids in the diatoms but less than 20% in I. galbana. Medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 40 publications
2
25
2
4
Order By: Relevance
“…Our results are in agreement with those reported by others (e.g. Moureute et al, 1990;Napolitano et al, 1990). No significant qualitative difference in fatty acid composition was noted between nitrate or ammonium grown cells, or between N-deprived cells originating from these (Table 2).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with those reported by others (e.g. Moureute et al, 1990;Napolitano et al, 1990). No significant qualitative difference in fatty acid composition was noted between nitrate or ammonium grown cells, or between N-deprived cells originating from these (Table 2).…”
Section: Discussionsupporting
confidence: 94%
“…HUFA can be supplied directly or indirectly to fish larvae from various sources including Isochrysis galbana, Brachionus plicatilis and Artemia spp (Watanabe et al 1983, Opstad et al 1989, Napolitano et al 1990). Studies of the HUFA content of cod Gadus morhua have shown that both 20:5n-3 and 22:6n-3 are abundant in eggs and larvae, as well as nauplii of Calanus finmarchicus, an important food item for G. rnorhua larvae (Fraser et al 1988, Klungsoyr et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…, Napolitano et al . ) and 18:3ω3 in green algae (Ahlgren, Gustafsson & Boberg, ; Steinman et al ., ; Torres‐Ruiz et al ., ), it is important to understand how environmental change may affect the concentration and composition of these limiting resources.…”
Section: Introductionmentioning
confidence: 99%